2016
DOI: 10.1044/2016_jslhr-l-15-0257
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Effects on Early Adolescent Language: A Twin Study

Abstract: Purpose We evaluated genetic and environmental contributions to individual differences in language skills during early adolescence, measured by both language sampling and standardized tests, and examined the extent to which these genetic and environmental effects are stable across time. Method We used structural equation modeling on latent factors to estimate additive genetic, shared environmental, and nonshared environmental effects on variance in stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…In contrast to the consistent effects observed for environmental risk factors, our study found limited evidence of the impact of genetics on SLCN acquisition in infancy. These findings are consistent with the literature which investigated longitudinal patterns of speech and language acquisition using studies of twins [ 4 , 13 ]. The authors found that shared environmental influences appear to be dominant in early language, with a smaller though significant role for genetic factors [ 4 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast to the consistent effects observed for environmental risk factors, our study found limited evidence of the impact of genetics on SLCN acquisition in infancy. These findings are consistent with the literature which investigated longitudinal patterns of speech and language acquisition using studies of twins [ 4 , 13 ]. The authors found that shared environmental influences appear to be dominant in early language, with a smaller though significant role for genetic factors [ 4 ].…”
Section: Discussionsupporting
confidence: 92%
“…There are several theoretical frameworks which seek to explain the underlying complexity of a child’s developmental landscapes [ 1 ]. In the economics literature, the “Heckman theory” or theory of “human capital development” suggests that an individual’s rate of development is determined by an initial vector of “skills and abilities”, which is largely determined by a complex interaction of biological factors (genetic, in utero environment and early infant health status) [ 2 , 3 , 4 , 5 , 6 , 7 ] and social factors (cultural, familial, socio-economic, community) [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Low language is a significant early childhood development concern, which is viewed as a “health shock” to a child’s initial vector of “skills”.…”
Section: Introductionmentioning
confidence: 99%
“…These survey findings have important implications for clinical practice. Underuse of contextualized and activity-focused language assessments creates risk that language difficulties at a discourse level will be under-identified (Ebert & Scott, 2014;Harlaar et al, 2016;Thomas-Stonell et al, 2013) whilst underuse of dynamic assessments and assessments that target school and home/community contexts may lead to intervention goals and classroom supports that are not well-matched to a child's needs (Bishop & McDonald, 2009;Kover et al, 2014). Similarly, the use of norm-referenced measures rather than use of dynamic assessments with children from CALD backgrounds may lead to inappropriate conclusions being drawn regarding the language abilities of these children (Caesar & Kohler, 2007).…”
Section: Objective 1 Regularity Of Assessment Usementioning
confidence: 99%
“…The ICF provides a framework for describing health and wellbeing across multiple components including Body Functions and Structures (impairment), Activities (execution of tasks), Participation (involvement in daily life activities), Environmental Factors and Personal Factors and as such, has been identified as an important framework for conceptualizing SLP assessment practice. Applying the ICF requires SLPs to use assessments that collect data on a child's performance in different types of tasks, such as de-contextualized, contextualized or activity-focused tasks (Denman et al, 2019;Harlaar et al, 2016) and on a child's performance across different environmental contexts, including a clinical context, school context or home/community context (Denman et al, 2019;Kover et al, 2014) in order to best understand a child's language performance at a holistic level (Westby, 2007). This is important as children may perform differently depending on the types of tasks targeted in an assessment (Thomas-Stonell et al, 2013;Trembath et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation